Refractory depressive disorder as the first manifestation of adolescent Sjögren’s syndrome, successfully treated with rituximab - Amal El-Ouakhoumi; Hajar Joulal; Jaouad Yousfi; Laila Benjilali; Mouna Zahlane; Lamiaa Essaadouni (European Journal of Case Reports in Internal Medicine, 2024)
Background: The psychiatric manifestations of Sjögren’s syndrome are often overlooked despite their prevalence. They can be revelatory of the disease and include anxiety, depression, dementia and, rarely, psychosis. Case description: We report a case of 18-year-old female in whom a major depressive syndrome revealed primary Sjögren’s disease, with a favourable outcome after treatment with rituximab. Conclusion: The diagnostic of Sjögren’s syndrome should be considered in patients who present with unexplained and refractory neuropsychiatric symptoms, even in the absence of sicca symptoms.